Explaining email use at UiTM with technology acceptance model - Denan, Zarina; Aliman, Sharifah (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2005)
This is a correlational study that examines the factors influencing the use of email in the workplace among UiTM staff. The Technology Acceptance Model (TAM) was used in this study as the conceptual framework. This study seeks to examine the relationships between perceived usefulness and intention to use, perceived ease of use and intention to use, perceived usefulness and perceived ease of use, subjective norm and perceived usefulness, and power distance and perceived usefulness. The results of this study show that there are strong relationships between perceived usefulness and intention to use, perceived ease of use and intention to use, and perceived ease of use and perceived usefulness. The relationships of social influence processes (subjective norm and power distance) with perceived usefulness were not significant. These findings contradict the findings of Huang et al. (2003) from the People's Republic of China. It can be concluded that although Malaysians (specifically UiTM staff) are considered to have high power distance (Currie, 1991), they are not easily influenced by superiors regarding technology adoption. From this study, it is evident that opportunities exist for UiTM to realize a deeper, wider, and more productive organization by fostering greater technology acceptance. This study will also assist UiTM management in better understanding its users' (staff) adoption behavior. Generally, UiTM staff possess the intention to use email because they perceive it as useful and beneficial. It is anticipated that more user-friendly and useful technology will be widely accepted at UiTM.